Copolymers Possessing Dithienothiophene and Boron for Optoelectronic Applications - EROĞLU, MEHMET SAYIP (WILEY-BLACKWELL, 2016)
In this work, copolymers of dithienothiophenes (DTT) and DTT-4,4-dioxide (DTT-S,S-O-2) with mesitylboron were prepared for optoelectronic applications. Optical and electro-chemical investigations were performed giving rise to the band gaps of 2.46-3.21 and 2.18-2.88 eV, respectively. Copolymers possessing DTT-S,S-O-2 units demonstrated the lower band gaps. Density functional theory investigations of the model compounds revealed the presence of an intramolecular charge transfer transition between the donor DTT units and the boron acceptor atoms. (C) 2016 Society of Plastics Engineers
Keywords: ORGANOBORON POLYMERS; DENSITY; TRANSISTORS; OLIGOMERS; REAGENT; DONOR